Impact of H+ ion irradiation on near-surface microstructure of 316H stainless steel fabricated via powder bed fusion - Mahmoud A. Mahrous; Muhammad A. Abdelghany; Mohamed Aboukhatwa; Iwona Jasiuk (Journal of Materials Research and Technology)
This study examines the near-surface microstructural evolution of 316H stainless steel produced via additive manufacturing (AM 316H SS) using laser powder bed fusion, compared to conventionally manufactured 316H stainless steel (standard 316H SS), following irradiation with 0.5 MeV H+ ions at room temperature up to 6.0 dpa. This focus on the near-surface region is crucial for applications where surface properties are critical under irradiation. Using electron backscatter diffraction (EBSD) and backscattered electron (BSE)/energy-dispersive X-ray spectroscopy (EDS), distinct pore morphologies were identified in AM 316H SS, with surface defects showing iron (Fe) depletion and chromium (Cr) and nickel (Ni) segregation. Notably, AM 316H SS exhibited superior radiation resistance, retaining its elemental composition with minimal degradation, while standard 316H SS displayed significant surface deterioration and grain fragmentation. EDS analysis confirmed Fe content in AM 316H SS increased slightly (65.73 %–65.93 %) and Cr decreased minimally (16.98 %–16.88 %). In contrast, standard 316H SS exhibited considerable silicon enrichment (97.29 % increase) and trace phosphorus. These findings underscore the stability of AM 316H SS under irradiation, highlighting its potential for harsh radiation environments.